Agronomic and yield selection of doubled haploid lines of rainfed lowland rice in advanced yield trials - Miftahur Rizqi Akbar; Bambang Sapta Purwoko; ISWARI SARASWATI DEWI; WILLY BAYUARDI SUWARNO; SUGIYANTA SUGIYANTA; MUHAMMAD FUAD ANSHORI (Society for Indonesian Biodiversity, 2021)
Abstract. Akbar MR, Purwoko BS, Dewi IS, Suwarno WB, Sugiyanta, Anshori MF. 2021. Agronomic and yield selection of doubled haploid lines of rainfed lowland rice in advanced yield trials. Biodiversitas 22: 3006-3012. Selection process is important step to obtain high yielding variety. This study aimed to obtain information on agronomic performance of doubled haploid lines of rainfed rice in advanced yield trials and select the best lines for multi-location yield trials. Two experiments were conducted in Bogor and Subang using a randomized complete block design for each location and consisted of 35 doubled haploid lines and two check varieties namely Ciherang and Inpari 18 as a treatment. The result revealed that interaction between genotype and environment (G x E) significantly affected all agronomic characters, except on the panicle length. Characters with high heritability value were all agronomic characters except number of productive tillers and productivity. Genotypic correlation analysis showed that number of productive tillers and weight of 1000 grains had significant and positive correlation with productivity. The selection used weighted selection index based on multivariate analysis. Fourteen lines were selected for multi-location yield trials. These lines had characteristics as follows: number of productive tillers (14.0-17.7 tillers), weight of 1000 grains (24.7-32.5 g), and productivity (5.0-6.2 ton ha-1). The selected lines can be evaluated further to obtain superior lines in multi-location trials.